Creation of a family medicine residency blog. (November 2018) - Jones, Kyle Bradford; Fortenberry, Katherine; Sanyer, Osman; Knighton, Rachel; Van Hala, Sonja
Objective: To describe the process of creating the Family Medicine Vital Signs blog, curated and edited by residents and faculty at the University of Utah Family Medicine Residency Program and to obtain feedback from participants regarding educational impact. Methods: Each resident and faculty member contributes at least one blog post per year (with other invited authors), resulting in one post per week on the blog site. An editorial board composed of residents and faculty provides direction and editorial assistance for each post. Residency staff assist in providing authors with reminders and logistical support. A survey was conducted of blog contributors to understand their perceptions of the blog's educational value. Results: The Family Medicine Vital Signs blog was started in July 2014, with 40% (n = 68) of the 170 posts provided by residents, 38.2% (n = 65) by faculty, and 21.8% (n = 37) by invited authors through June 2017. It has averaged nearly 100 unique readers per week and has had 15 posts republished in different venues. The participant survey demonstrated scores above the median-possible score, showing positive impact in support of the educational goals. Conclusion: A residency blog provides a venue for educational instruction, supporting physician development of communication skills, community engagement, and advocacy.